Pharmacokinetics, Pharmacodynamics, and Pharmacogenetics of Efavirenz 400 mg Once Daily During Pregnancy and Post-Partum - Lamorde, Mohammed; Wang, Xinzhu; Neary, Megan; Bisdomini, Elisa; Nakalema, Shadia; Byakika-Kibwika, Pauline; Mukonzo, Jackson K.; Khan, Waheed; Owen, Andrew; McClure, Myra; Boffito, Marta (Clinical Infectious Diseases, 2018)
A clinical trial showed that efavirenz 400 mg once daily (EFV400) is as effective as the standard adult dose. World Health Organization recommends EFV400 as an alternative first-line agent, but data are lacking in the third trimester of pregnancy (TT). We investigated the pharmacokinetics, efficacy, and CYP2B6 pharmacogenetics in HIV-infected women (WLWH) on EFV400 during TT and post-partum (PP). Methods. An open-label 2-center study (United Kingdom, Uganda) was conducted in WLWH receiving antiretroviral regimens containing efavirenz 600 mg, who had their efavirenz dose reduced to EFV400. Weekly therapeutic drug monitoring (TDM), steadystate pharmacokinetic profiles (TT and PP), safety, virological efficacy, and CYP2B6 polymorphisms at positions 516 (C > T) and 938 (T > C) were evaluated.
Keywords: Low-dose efavirenz; Pharmacokinetics; Pregnancy